2008
DOI: 10.1103/physreva.77.052322
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement of finite cyclic chains at factorizing fields

Abstract: We examine the entanglement of cyclic spin 1/2 chains with anisotropic XY Z Heisenberg couplings of arbitrary range at transverse factorizing magnetic fields. At these fields the system exhibits a degenerate symmetry-breaking separable ground state (GS). It is shown, however, that the side limits of the GS pairwise entanglement at these fields are actually non-zero in finite chains, corresponding such fields to a GS spin-parity transition. These limits exhibit universal properties like being independent of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
195
0
44

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(252 citation statements)
references
References 23 publications
13
195
0
44
Order By: Relevance
“…Not only. It is well known that, in the thermodynamic limit, the expectation value of an operator that commutes with the parity is the same if evaluated on |e {γ} or on |o {γ} [25,26,30]. We indicate such expectation value on one of the symmetric ground states as Ô {µi}…”
Section: A Quantitative Approach To the Distinguishabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Not only. It is well known that, in the thermodynamic limit, the expectation value of an operator that commutes with the parity is the same if evaluated on |e {γ} or on |o {γ} [25,26,30]. We indicate such expectation value on one of the symmetric ground states as Ô {µi}…”
Section: A Quantitative Approach To the Distinguishabilitymentioning
confidence: 99%
“…In the magnetically ordered phases of a one dimensional system made by spin-1/2, the Hamiltonian admits a twofold degenerated ground states [25,26]. Among all the others, there will be two ground states that are also eigenstates of the parity with opposite eigenvalues.…”
Section: A Quantitative Approach To the Distinguishabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The Hamiltonian (46) commutes with the S z spin parity operator P z , irrespective of the coupling range, anisotropy, dimension or geometry of the system [55][56][57],…”
Section: Model and General Expressionsmentioning
confidence: 99%
“…It is first shown that in contrast with the pair entanglement, the quantum discord and the information deficit exhibit, for the exact ground state of these chains, common features, such as an appreciable finite value below the critical field, for all separations. Moreover, they approach a finite common non-zero value [44] at the remarkable factorizing field [49,50,[53][54][55][56][57][58][59][60] that these chains can exhibit in the anisotropic case. On the other hand, we will also show that important differences between the quantum discord on the one side and the standard and generalized information deficit on the other side do arise in the minimizing local spin measurement that defines them.…”
Section: Introductionmentioning
confidence: 99%